The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1038/nn979
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger protein too few controls the development of monoaminergic neurons

Abstract: The mechanism controlling the development of dopaminergic (DA) and serotonergic (5HT) neurons in vertebrates is not well understood. Here we characterized a zebrafish mutant--too few (tof)--that develops hindbrain 5HT and noradrenergic neurons, but does not develop hypothalamic DA and 5HT neurons. tof encodes a forebrain-specific zinc finger transcription repressor that is homologous to the mammalian Fezl (forebrain embryonic zinc finger-like protein). Mosaic and co-staining analyses showed that fezl was not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
105
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 29 publications
4
105
0
Order By: Relevance
“…Within the brain proper, one case of such a mechanism was also reported recently: the control of the number of catecholaminergic and serotonergic neurons in the zebrafish hypothalamus by the zinc finger transcription factor Too few/Fezl (Levkowitz et al, 2003). This process is non-cell-autonomous and does not affect forebrain patterning (Levkowitz et al, 2003). The regulation of six3 cluster size that we unravel here, thus, provides a second example of such a mechanism during primary neurogenesis within the brain proper.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Within the brain proper, one case of such a mechanism was also reported recently: the control of the number of catecholaminergic and serotonergic neurons in the zebrafish hypothalamus by the zinc finger transcription factor Too few/Fezl (Levkowitz et al, 2003). This process is non-cell-autonomous and does not affect forebrain patterning (Levkowitz et al, 2003). The regulation of six3 cluster size that we unravel here, thus, provides a second example of such a mechanism during primary neurogenesis within the brain proper.…”
Section: Discussionsupporting
confidence: 75%
“…In this case, the signaling and relay process involved were identified: nodal signaling from the PCP promotes the production of Shh by optic stalk tissue, which in turn regulates retinal ath5 expression (Masai et al, 2000). Within the brain proper, one case of such a mechanism was also reported recently: the control of the number of catecholaminergic and serotonergic neurons in the zebrafish hypothalamus by the zinc finger transcription factor Too few/Fezl (Levkowitz et al, 2003). This process is non-cell-autonomous and does not affect forebrain patterning (Levkowitz et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The zinc-finger transcriptional repressor Fezl (forebrain embryonic zinc-finger-like protein) (12)(13)(14) is expressed in cortical layers 5 and 6 (15). In zebrafish, both ectopic expression and loss-of-function analyses suggest that Fezl regulates gene expression in the ventral forebrain (14) and the development of dopaminergic and serotonergic neurons (16). Based on the expression of Fezl in the deep layers of the cerebral cortex and functional data from zebrafish, we hypothesized that Fezl regulates the specification or differentiation of layer 5 and 6 neurons during mammalian cortical development.…”
mentioning
confidence: 99%
“…Therefore, understanding the determination of DA phenotype and the specification of DA neuronal circuitry may provide mechanistic and therapeutic insights into these disorders. To date, only limited number of known or putative transcriptional regulators, including Pax6, Dlx, Nurr1, Lmx1a, Lmx1b, Msx1, Foggy, and Too Few (Tof͞Fez1), have been implicated in the specification of DA phenotype in vertebrates (2)(3)(4)(5)(6)(7)35). Despite this knowledge, the mechanisms leading to the early commitment of pluripotent neural stem cells to DA lineage remain elusive.…”
mentioning
confidence: 99%
“…Molecular characterizations have revealed that the too few mutant carries a point mutation that changes Cys-287 to Ser in the second of the six zinc finger motifs of the conserved zinc finger protein Fezl (Tof͞Fezl) (5). Whereas these studies establish an important role of Tof͞Fezl in DA neuron development, the mechanism by which Tof͞Fezl acts in DA neuron specification is not clear.…”
mentioning
confidence: 99%